Application of Family Nursing Care in Patients with Hypertension: A Case Study - Chairani, Reni; Satriadi, Alif (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Hypertension contributes to nearly 9.4 million deaths from cardiovascular disease every year. It also increases the risk of coronary heart disease by as well as increases the risk of stroke. Hypertension can also cause economic losses, the incidence of chronic diseases will directly reduce the number of the workforce due to high mortality, work absenteeism, disability and early retirement. Nurses have an important role to help families in the management of hypertension. Nurses have a role in changing behavior as an effort to reduce the risk of rising blood pressure and one of the treatments is the application of family nursing care. Objective: To determine the effectiveness of implementing family nursing care for hypertensive patients as an effort to reduce blood pressure. Research Methods: This research design uses a case study method that implements the application of family nursing care to hypertensive patients as an effort to reduce blood pressure. This study was conducted on hypertensive patients in the family of Mr.G Rt 02/03 Parigi Village, Cikande District, Serang Regency. Results: The application of family nursing care for 4 visits can increase patient knowledge about hypertension, reduce acute pain with relaxation techniques, overcome sleep patterns by doing breathing techniques before going to bed and reduce blood pressure from 140/95mmhg to 130/90mmhg. Conclusion: Family nursing care is effective in lowering blood pressure.